Effect of synthetic and food waste-derived volatile fatty acids on lipid accumulation in Rhodococcus sp. YHY01 and the properties of produced biodiesel. (15th July 2019) - Bhatia, Shashi Kant; Gurav, Ranjit; Choi, Tae-Rim; Jung, Hye-Rim; Yang, Soo-Yeon; Song, Hun-Suk; Kim, Yun-Gon; Yoon, Jeong-Jun; Yang, Yung-Hun
Graphical abstract: Highlights: Rhodococcus sp. YHY01 can utilize volatile fatty acids as carbon source. Acetate, butyrate and lactate play role in even number fatty acids synthesis. Propionate directly involved in synthesis of odd carbon number fatty acids. Higher biomass and fatty acid yield coefficient obtained with butyrate. Food waste derived volatile fatty acids are a suitable feedstock for biodiesel production. Abstract: Food waste-derived volatile fatty acids (VFAs) can act as a renewable feedstock for biodiesel production. In synthetic media, Rhodococcus sp. YHY01 was able to utilize various organic acids (acetate, butyrate, lactate, and propionate) as a carbon source. Butyrate was the optimal carbon source, having a minimum inhibitory effect on growth, and a maximum growth yield coefficient (Yx/s 0.288 g dcw/g butyrate) and fatty acid yield coefficient (Yf/s 0.206 g/g butyrate), compared to other organic acids (lactate, propionate, and acetate). Acetate, butyrate, and lactate mostly supported the production of fatty acids with an even number of carbons, whereas propionate enhanced the content of odd-numbered fatty acids. Response surface methodology (RSM) design study resulted in maximum biomass (2.8 g/L) and fatty acid yield (1.9 g/g) with acetate:butyrate:lactate (0.333:0.333:0.333) as a carbon source. Culture of Rhodococcus sp. YHY01 in media containing food waste-derived VFAs as the carbon source had a biomass (3.2 g dcw/L), fatty acid yield (2.2 g/L), and fatty acid accumulation (69% w/w) under nitrogen-limited condition. Biodiesel produced from food waste had an iodine value (IV, 37), cetane number (CN, 63), high heating value (HHV, 39), density (υ, 3.9), and viscosity (ρ, 0.868) that meet international standards.